Ponds in UTHM: Water Criteria and Quality - Azwan, Amezuddin; Norazman, Amir Fahim; Seswoya, Roslinda; Pa'ee, Furzani (Journal of Advancement in Environmental Solution and Resource Recovery, 2021)
Invasive aquatic plants (IAP) in the river/stream or lake are typically grown. IAP was left along the river/stream/lake after maintenance and clearance, caused the unpleasant view. The excessive nutrients in the water can cause native plants to have unusually high growth rates, the natural density and distribution of aquatic plants in lakes and streams can become affected. Ammoniacal nitrogen are the most nutrients that can be found in a water body. Despite the significance of these nutrients for aquatic health, severe problems may also arise from overabundance of nutrient. This study is limited to several ponds in UTHM. The objectives of the research are to identify type of aquatic plant that exist in pond and to determine the water quality of the pond. The water quality measurements involved the ammonia nitrogen and total suspended solid by following Method 8038 Nessler’s and Standard Method 2540, APHA. The water quality also be determined using subindex of ammoniacal nitrogen and total suspended solid. The result showed that water lily grows in two ponds. The ammoniacal nitrogen from three ponds are different, subsequently resulted in different class such Class II, III and IV. However, using total suspended solid as a reference, each pond was classified as Class 1. Pond B was consistently showing the clean water quality status as based on subindex of ammoniacal nitrogen and total suspended solid.